POTENSI BERPIKIR KREATIF PESERTA DIDIK DALAM PEMECAHAN MASALAH MATEMATIS BERDASARKAN TEORI WALLAS DI SMP - Nurwahyuni, Nurwahyuni; Sugiatno, Sugiatno; Ahmad, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe purpose of this research was to describe the potency of students creative thinking in solving mathematical problems in geometry based on Wallas Theory in class VII SMP N 3 Batu Ampar viewed based on their ability level. The form of research used to descriptive research with qualitative data. The subjects in this research were six students of class VII A. Data collection methods obtained from written tests to determine students creative thinking processes; the final grade of mathematics in an odd semester and the opinion of mathematics teacher to find out the level of mathematical ability of students; and interviews to bring out the potency for more considerable creative skill. This research indicated that R1 students have high skill, R2 has moderate strength, and R3 has low ability. This research showed that the process of creative thinking include stages of expressing ideas in their sentences, looking back and planning the concepts of problem-solving, solving the problems based on the ideas has they are made, and rechecking their answer. The result of the research also showed that each student has different potency for creative thinking.Keywords: Creative Thinking Potency, Mathematical Problem Solving, Wallas Theory